Emerging debates on labor and privacy matters: video surveillance systems, digital algorithms and biometric identification of the worker - Aragüez Valenzuela, Lucía (2021)
Information and communication technologies have revolutionized the world of labor by strengthening, among other things, the power of corporate surveillance. This has affected workers’ most basic rights, including their privacy, in a way that is certainly invasive. This corporate control through technological tools is sometimes not entirely transparent or honest, and can even invade the worker’s private sphere in an inadvertent way.In this article, the author reflects on these topics that, in turn, are the subject of certain controversies at the doctrinal and jurisprudential level, trying to provide a critical perspective in favor of greater protection for the working person and a strengthening of the regulations existing labor.